A proprietary black cumin oil extract (Nigella sativa) (BlaQmax®) modulates stress-sleep-immunity axis safely: Randomized double-blind placebo-controlled study - Mohan, Muttanahally Eraiah; Thomas, Jestin V.; Mohan, Mohind C.; Das S, Syam; Prabhakaran, Prathibha; Pulikkaparambil Sasidharan, Baby Chakrapani (Frontiers in Nutrition, 2023)
Objective Stress, sleep, and immunity are important interdependent factors that play critical roles in the maintenance of health. It has been established that stress can affect sleep, and the quality and duration of sleep significantly impact immunity. However, single drugs capable of targeting these factors are limited because of their multi-targeting mechanisms. The present study investigated the influence of a proprietary thymoquinone-rich black cumin oil extract (BCO-5) in modulating stress, sleep, and immunity. Methods A randomized double-blinded placebo-controlled study was carried out on healthy volunteers with self-reported non-refreshing sleep issues (n = 72), followed by supplementation with BCO-5/placebo at 200 mg/day for 90 days. Validated questionnaires, PSQI and PSS, were employed for monitoring sleep and stress respectively, along with the measurement of cortisol and melatonin levels. Immunity markers were analyzed at the end of the study. Results In the BCO-5 group, 70% of the participants reported satisfaction with their sleep pattern on day 7 and 79% on day 14. Additionally, both inter- and intra- group analyses of the total PSQI scores and component scores (sleep latency, duration, efficiency, quality, and daytime dysfunction) on days 45 and 90 showed the effectiveness of BCO-5 in the improvement of sleep (p < 0.05). PSS-14 analysis revealed a significant reduction in stress, upon both intra (p < 0.001) and inter-group (p < 0.001) comparisons. The observed reduction in stress among the BCO-5 group, with respect to the placebo, was significant with an effect size of 1.19 by the end of the study (p < 0.001). A significant correlation was also observed between improved sleep and reduced stress as evident from PSQI and PSS. Furthermore, there was a significant modulation in melatonin, cortisol, and orexin levels. Hematological/immunological parameters further revealed the immunomodulatory effects of BCO-5. Conclusion BCO-5 significantly modulated the stress-sleep-immunity axis with no side effects and restored restful sleep.